Sifat pro-oksidan perasan jeruk lemon (Citrus Limun L.) untuk meningkatkan aktivitas antioksidan teh hitam: Prooxidant properties of lemon extract (Citrus Limun L.) to increase antioxidant activity of black tea - Anggraeni, Frida Dwi; Suprihana (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2024)
Black tea was a drink made through fermentation by the enzyme polyphenol oxidase which could enzymatically oxidize catechins in fresh leaves. Lemon juice was added to the tea to determine the effect of adding lemon juice to the tea. This research aimed to determine the effect of brewing temperature and the pro-oxidant properties of adding lemon juice on changes in polyphenols and antioxidant activity of black tea. This research used a factorial design with 2 treatment factors, namely black tea brewed at 80oC and 100oC with the addition of 0%, 1% and 2% lemon juice with 3 repetitions. Green tea was used as a control. Analysis was carried out on total phenol content and IC50. Data analysis used the ANOVA test with a confidence level of 0.05. The research results showed that the total phenol of steeping black tea at a temperature of 80oC were lower than those steeping black tea at a temperature of 100oC, namely 20.41% and 27.08% respectively, but lower than the total phenol of green tea. Likewise, the higher level of added lemon juice, the higher total phenol content, but lower than total phenol content of green tea. For antioxidant activity was measured by IC50 inhibition, it showed that IC50 value at a black tea steeping temperature of 100oC was lower than IC50 value at 80oC black tea steeping. Likewise, with the addition of lemon juice, IC50 value decreased, namely 65.75 µg/ml to 35.84 µg/ml for steeping black tea at 80oC and 22.88 µg/ml to 15.94 µg/ml for steeping black tea at 100oC. The smaller IC50 value, the higher antioxidant activity.